Avaliação do efeito antifúngico de derivados triazólicos obtidos por estratégia de hibridação molecular - Silva, Jéssica Adalgisa Barbosa (2024)
Black pepper has been increasingly gaining ground in the international market, accounting for 98% of Brazilian pepper exports. Espírito Santo is the most prominent state in Brazil as a black pepper producer, contributing 60% of the country's production of this spice. However, this cultivation is frequently threatened by the fungus Fusarium solani, which causes root rot in the plants. With the aim of producing new promising molecules against this pathogen, novel triazole compounds derived from natural products were synthesized. Initially, the azido-adamantane derivatives 20 and 23 were obtained and subsequently combined with alkynes derived from natural products, such as isatin, p-coumaric acid, eugenol, and thymol, to form the 1,4-disubstituted 1,2,3- triazole ring. Therefore, in this study, six molecular hybrids were designed through the copper(I)-catalyzed azide-alkyne cycloaddition reaction (CuAAC), also known as "Click Chemistry," in the presence of copper(II) sulfate pentahydrate and sodium ascorbate. The compounds 25a-b and 26a-d were characterized by 1H NMR, 13C, COSY, HMQC, HSQC, and infrared spectroscopy (FTIR) and achieved yields ranging from 20.35% to 63.66%. Molecular docking studies between the synthesized compounds and the enzyme Succinate Dehydrogenase (SDH), PDB: 1NEN, indicated that compounds 26b and 26d are potential SDH inhibitors, with hydrogen bond interactions analogous to those of the original ligand DNT, involving the amino acid residues TYR83, TRP164, and ARG31.